2011
DOI: 10.1111/j.1479-828x.2011.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the Perigee™ system for treatment of cystocele – our five‐year experience

Abstract: In this five-year experience, the Perigee™ system is deemed safe with an acceptable recurrence risk rate and complication rate. Further randomised controlled trials comparing Perigee™ system with traditional anterior colporrhaphy should be performed to evaluate mesh-based surgery safety and efficacy for level one evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Erosion rates with other apical and anterior correction systems are similar: Letouzey et al found a rate of 2.7 % using the Uphold system, and De Landsheere et al found a rate of 2.5 % using the Prolift system [26,29]. In a prospective study of the Perigee system in 376 patients, the erosion rate was higher, at 11.1 % [24]. Vaginal pain was defined as pain provoked on vaginal examination.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Erosion rates with other apical and anterior correction systems are similar: Letouzey et al found a rate of 2.7 % using the Uphold system, and De Landsheere et al found a rate of 2.5 % using the Prolift system [26,29]. In a prospective study of the Perigee system in 376 patients, the erosion rate was higher, at 11.1 % [24]. Vaginal pain was defined as pain provoked on vaginal examination.…”
Section: Discussionmentioning
confidence: 91%
“…Moore et al, in 114 patients with anterior wall prolapse of stage ≥2 managed using the Perigee system, found an objective success rate of 88.5 %, but without apical assessment [23]. In a prospective study in 376 patients with cystocele of stage ≥3 managed with the Perigee system, Rane et al found a success rate of 94.3 % in the anterior compartment at 5 years [24]. Only Lo et al, in patients with pelvic organ prolapse, 57 managed with the Elevate Ant system and 61 with the Perigee system, found significantly better point-C correction at 1 year with the Elevate Ant system (8.07 preoperatively versus −10.50 at 1 year) compared with the Perigee system associated with sacrospinous fixation (p < 0.001) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Safety and efficacy of the Perigee TM system have been documented with recent five-year data. 8 However, failure (that is, pullthrough) of those anchoring arms is not uncommon. 9 Due to increasing emphasis on the importance of apical support for the anterior compartment, 10 mesh kit systems such as the Anterior Elevate TM (American Medical Systems) were introduced.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Cystocele [anterior vaginal wall prolapse (AVWP)] is the most common type of POP in women and is due to herniation of the bladder through anterior vaginal wall. [3] It may be lateral or central due to loss of support or weakness of the pubocervical facia between bladder and vagina. [4] Female stress urinary incontinence (SUI) is a significant health problem which is considered to be a common condition for adult female with prevalence rates ranging from 12.8 to 46%.…”
Section: Introductionmentioning
confidence: 99%